UJARAN KEBENCIAN DALAM UNDANG-UNDANG NOMOR 7 TAHUN 2017 TENTANG PEMILU DAN TINJAUAN SIYASAH DUSTURIYAH - Ulya Permatasari; Ulya Atsani; Muhammad Hizbi Islami (Al Ushuliy: Jurnal Mahasiswa Syariah dan Hukum, 2023)
The main problem in this thesis is the regulation of hate speech in Law Number 7 of 2017, because when the agenda for a democratic party or also known as elections is approaching, the behavior of hate speech has greatly increased. Certain groups of candidates may clash with other supporting groups, so that Article 28E paragraph (3) of the 1945 Constitution of the Republic of Indonesia, "everyone has the right to freedom of association, assembly and expression of opinions", is very vulnerable to dealing with the right to freedom of opinion and expression. The purpose of this study is to find out more about the regulation of hate speech in Law Number 7 of 2017 concerning general elections and siyasa dusturiyyah reviews. To answer the object of the study, the authors used library research using a normative juridical approach with statutory and conceptual approaches. In this case, it includes primary legal materials, namely from laws and regulations, especially Law Number 7 of 2017 concerning Elections and secondary legal materials from legal and Islamic books and journals. In the research that the authors conducted, it can be concluded that, until now, hate speech in elections in Indonesia has not been clearly interpreted, even in Law Number 7 of 2017 concerning General Elections (Elections) it is not explained in detail regarding how to define, victims, perpetrators, sanctions imposed as well as benchmarks or limitations that can be categorized as hate speech in elections. Law Number 7 of 2017 concerning Elections in fiqh siyasa dusturiyyah, the source of its formation is siyasah wad'iyah because it is produced by mere human thought products which in the drafting process do not pay attention to norms and ethics. Hate speech in Islam is a prohibited act because it can cause harm, especially to the soul, and in it has an element of humiliation, namely lowering one's self-esteem/soul, which should be maintained or guarded for every human being from any group as per the concept of the formulation of the basis of the state (fiqh siyasa dusturiyyah). and the principle is to prioritize guarantees of human rights and realize justice.